Genetic characterisation and forensic importance of 20 Y-STRs in Han population from Anshan, Northeast of China. (3rd July 2020) - Diao, Yefang; Adnan, Atif; Lin, Qin; Sun, Chang; Wang, Lie
Abstract: Background: With a population of over 1.4 billion and 56 ethnic groups, China is the largest country in the world in terms of population. Han is the main ethnic group of China (93%). Aim: To provide genetic data of Y chromosomal STRs from Anshan City, Northeast of China, for the first time, which will serve as a reference database for forensic and population studies. Subjects and methods: We report data of 20 Y-chromosomal short tandem repeats (YSTRs) genotyped with the Goldeneye ® 20Y kit in 270 Han individuals residing in Anshan City of China. Results: A total of 170 alleles were observed on 20 Y-STRs. The gene diversities varied from 0.3460 (DYS391) to 0.9692 (DYS385). Overall haplotype diversity was almost 1 with 261 unique haplotypes, while the discrimination capacity (DC) was 0.9814. Pairwise Rst and Fst genetic analyses, MDS plot, N-J tree and PCA showed the genetic structure of Anshan Han population was significantly different from other minority groups like Tibetans and Kazakhs. Conclusions: Results of this study showed that Goldeneye ® 20Y system loci have strong discriminatory power in the Anshan Han population of China which makes this kit suitable for forensic applications in this ethnic group.